Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Pupuk Npk Non Subsidi Dikecamatan Binjai Hulu Kabupaten Sintang (Jurnal Social Economic of Agriculture, 2017)
The main objective of this research is to : Assess the factors that influence the consumers purchase decisions of non-subsidized NPK fertilizer in of Binjai Hulu Sintang.This study was conducted using a case study with survey techniques . Locations were selected intentionally ( purposive) that is in the district of Binjai Hulu Sintang. Methods of data analysis used Konfirmatory Factor Analysis. Research variables is the marketing mix, of product, price, place, and promotion.The extraction of analysis the research variables all the items variable has a value of ≥ 4 so that it can be seen that all of variable that consumers consider the purchase of non-subsidized NPK fertilizer products in Binjai Hulu Sintang.Based on analysis of factors, factors forming Purchase Decision , Product Identity factor ( X1 ) have the most influence on purchasing decisions with a correlation coefficient of 0.751 , followed by a factor of Point of Sale ( X4 ) with a correlation coefficient of 0.707 , a factor Product Price ( X3 ) with a correlation coefficient of 0.673 , and the smallest influence is a factor Product Information ( X2 ) with a correlation coefficient - 0,523 .Keywords : Marketing Mix, purchase decision, non-subsidized NPK fertilizer